1991
DOI: 10.1104/pp.96.3.806
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Promotes Elongation Growth and Auxin Promotes Radial Growth in Ranunculus sceleratus Petioles

Abstract: Submergence induces elongation in the petioles of Ranunculus sceleratus L

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…Thus, this species contrasts with Regnellidium diphyllum, Ranunculus sceleratus and Nymphoides peltata, in which auxin is required for ethylene action (Walters and Osborne, 1979;Horton and Samarakoon, 1982;Malone and Ridge, 1983). A combination of ethylene and auxin treatment of three aquatic plants, Regnellidium diphyllum, Hvdrocharis morsus-ranae and Ranunculus sceleratus showed that eth ylene and auxin effects are additive (Cookson and Osborne, 1978;Smulders and Horton, 1991) and both enhance elongation. Neither phenomenon was found in R. palustris.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this species contrasts with Regnellidium diphyllum, Ranunculus sceleratus and Nymphoides peltata, in which auxin is required for ethylene action (Walters and Osborne, 1979;Horton and Samarakoon, 1982;Malone and Ridge, 1983). A combination of ethylene and auxin treatment of three aquatic plants, Regnellidium diphyllum, Hvdrocharis morsus-ranae and Ranunculus sceleratus showed that eth ylene and auxin effects are additive (Cookson and Osborne, 1978;Smulders and Horton, 1991) and both enhance elongation. Neither phenomenon was found in R. palustris.…”
Section: Discussionmentioning
confidence: 99%
“…JA-Me inhibited elongation and radial growth promoted in petioles of Ranunculus scleratus by IAA and ethylene, respectively (Smulders and Horton 1991). Recently, it was found that IAA stimulated elongation growth of petiole and induced epinasty of intact Bryophyllum calycinum plants, and JA-Me greatly inhibited both processes (Ueda, Saniewski and Miyamoto, unpublished results).…”
Section: Inhibition Of Iaa-indu Ced Cell Elongationmentioning
confidence: 95%
“…96, 1996 Rumex pcilustris. In order to compare and validate our results, both Rumex palustris and Ranunculus sceleratus were used in similar experiments, since for the latter species auxin involvement has been clearly demon strated (Musgrave and Walters 1973, Cookson and Os borne 1978, Horton and Samarakoon 1982, Smulders and Horton 1991. The main objectives were to deter mine whether ( 1) the submergence-induced petiole elon gation o f Rumex palustris can be arrested by application of an auxin transport inhibitor, ageing of petiole tissue or removal of the lamina, (2 ) submergence results in a change in petiole responsiveness of Rumex palustris to wards auxin, and (3) the involvement of auxin in the submergence response of Rumex palustris and Ranuncu lus sceleratus is comparable.…”
mentioning
confidence: 99%